2020
DOI: 10.7185/geochemlet.2017
|View full text |Cite
|
Sign up to set email alerts
|

Past endolithic life in metamorphic ocean crust

Abstract: The known deep subsurface biosphere on Earth persists in diversified habitats, including deep within igneous rocks of the oceanic crust. Here, we extend the range of the deep subsurface biosphere to metamorphic ocean crust of a subduction zone. We report fossilised life in zeolite facies rocks, which formed by low grade metamorphism, from the southern Mariana trench. Dense carbonaceous spheroids, filaments, and Frutexites-like structures are preserved in these rocks, which are enriched in organic carbon but de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…53 The episodic release of fluids from the subducting slab along the fault structure could lead to the formation of serpentinite mud volcanoes in the forearc region above the hadal trench. 4,54,55 Growing evidence 4,47,56,57 has shown that the hydration of the incoming plate, subsequent dehydration of the incoming slab, and hydration of the mantle wedge of the overriding plate have profound impacts on sedimentary, geochemical, and biological processes in the hadal trench (Figure 4): (1) the hydration and dehydration of the hadal lithosphere could support fluid discharge and fuel chemolithoautotrophic life on the hadal seafloor and within the hadal lithosphere, [58][59][60] (2) the dehydration of the incoming plate could trigger earthquakes that substantially influence the sedimentary flux and organic carbon supply to the hadal trench, 61,62 and (3) the hydration/ alteration-derived sediments could increase the supply of carbon, iron, and other elements to the hadal trench and influence biogeochemical cycling therein. 63 Hydration of mantle lithosphere likely supporting fluid discharge It is well known that hydration of mantle rocks can drive the serpentinitehosted hydrothermal system at the deep-sea floor, which vents warm (40-90 C), high-pH (9-11) fluids enriched in H 2 and CH 4 that fuel chemolithotrophic life.…”
Section: Hadal Lithosphere Associated Fluids and Life Activities Hydration Of Hadal Lithospherementioning
confidence: 99%
See 4 more Smart Citations
“…53 The episodic release of fluids from the subducting slab along the fault structure could lead to the formation of serpentinite mud volcanoes in the forearc region above the hadal trench. 4,54,55 Growing evidence 4,47,56,57 has shown that the hydration of the incoming plate, subsequent dehydration of the incoming slab, and hydration of the mantle wedge of the overriding plate have profound impacts on sedimentary, geochemical, and biological processes in the hadal trench (Figure 4): (1) the hydration and dehydration of the hadal lithosphere could support fluid discharge and fuel chemolithoautotrophic life on the hadal seafloor and within the hadal lithosphere, [58][59][60] (2) the dehydration of the incoming plate could trigger earthquakes that substantially influence the sedimentary flux and organic carbon supply to the hadal trench, 61,62 and (3) the hydration/ alteration-derived sediments could increase the supply of carbon, iron, and other elements to the hadal trench and influence biogeochemical cycling therein. 63 Hydration of mantle lithosphere likely supporting fluid discharge It is well known that hydration of mantle rocks can drive the serpentinitehosted hydrothermal system at the deep-sea floor, which vents warm (40-90 C), high-pH (9-11) fluids enriched in H 2 and CH 4 that fuel chemolithotrophic life.…”
Section: Hadal Lithosphere Associated Fluids and Life Activities Hydration Of Hadal Lithospherementioning
confidence: 99%
“…A hypothesis that subduction zone zeolitefacies rock hosts Earth's deepest subsurface microbial ecosystems is proposed. 60 This is based on the fact that (1) zeolite-facies metamorphism starts at temperatures of approximately 40 C, well within the tolerance of life, and (2) zeolite-facies metamorphism can extend up to 14 km into the ocean crust of the subduction zone at temperatures below 121 C. To test this hypothesis, Peng et al 60 recovered zeolite-facies metamorphic rocks from the southern Mariana Trench at a water depth of 5,500 to 6,800 m using the manned submersible Jiaolong. Dense carbonaceous aggregates and filaments, which result from the past activity of chemolithoautotrophs, were observed to be preserved in those metamorphic rocks.…”
Section: Hydration Of Basaltic Lithosphere Supporting Fluid Dischargementioning
confidence: 99%
See 3 more Smart Citations